An Innovative Technique for Rapid Screening of Cigarette Filter Adsorbents - Branton, Peter; Leistner, Matthias; Woellner, Michelle; Kaskel, Stefan (Chemical Engineering & Technology, 2017)
Cigarette smoke is an aerosol containing a large number of chemicals, including toxicants. In recent years, a number of cigarette filter additives have been evaluated for their toxicant filtration properties. Screening is a useful tool to accelerate the testing and development of new filter additives and filtration mechanisms. The evaluation of a filter material screening technique based on the so-called InfraSORP technology is described. By comparing InfraSORP measurements with reference cigarette smoke experiments of potential cigarette filter materials like activated carbons and ion-exchange resin, an excellent correlation is demonstrated. This technique allows for a rapid screening of potential filter materials prior to testing any final candidates in cigarettes.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Activated carbon; Adsorption; Cigarette smoke; Filter additives; InfraSORP technology